IMPLEMENTASI TEKNOLOGI TEPAT GUNA BIOMACERATOR DALAM PENGOLAHAN BIOPESTISIDA LIMBAH TEMBAKAU DI DESA JATIAN, JEMBER - Naylatul Qiromi; Putri Safitri; Khoirun Nisya' Ulfiani; Firyaal Ulayya Al-Daan; Jodi Armansyah; Helda Wika Amini; Yukti Nurani; Ansori; Sonya Hakim Raharjo; Merymistika Yufrani Afred; Ratri Sekaringgalih; Nurul Hidayati (Jurnal Edukasi Pengabdian Masyarakat, 2026)
Jatian Village, Pakusari District, Jember Regency, has ±204,80 hectares of tobacco farmland, around 6.000 plants, and average production of 9,93 quintals of dried tobacco each season. About 18% of biomass becomes waste as inferior leaves and stems that remain unused and may pollute the environment. Yet tobacco waste contains active compounds such as nicotine, alkaloids, and flavonoids that can be used as raw materials for biopesticides. This program examined converting tobacco waste into biopesticide through maceration assisted by a biomacerator. The waste was chopped and dried, then macerated for 48 hours at a 3:7 material-to-solvent ratio using water-ethanol mixtures in two variations (9:1 and 9:2) to compare extraction effectiveness. Effectiveness tests showed that the 20% ethanol formulation accelerated mortality of armyworms within 3 minutes and grasshoppers within 45 minutes, whereas the 10% ethanol formulation required 10 minutes and 1 hour 20 minutes, respectively. The activity increased community understanding from 15% to 85%, enabled 85% of participants to operate the biomacerator independently, and achieved 95% satisfaction, indicating a sustainable solution that strengthens self-reliance in agricultural waste management.